Strength and fracture evolution characteristics of high fill canal levee soil - Huaichang YU; Jianhao ZHANG; Zirui WANG; Tianlong WU; Zhuoran WANG (Shuiwen dizhi gongcheng dizhi)
The splitting strength is one of the important factors affecting the stability of soil slope. Due to the different water sensitivity of different soils, the strength and deformation of soils under different water contents are different. To investigate the splitting strength characteristics and fracture evolution mechanism of expansive soil and modified soil under different initial water content, particle image velocimetry (PIV) technology was used to conduct a series of splitting tests on expansive soil and modified soil in the high fill canal embankment of the middle route of the South-to-North Water Transfer project in Nanyang City. The test results show that the load-displacement curves of expansive soil and modified soil have the same stage, but the stage characteristics are different under different water contents. The critical water content and peak load of the expanded soil sample are smaller than that of the modified soil sample, but the peak load of the two soils increases first and then decreases with the increase of water content, and has the characteristics of single peak. According to the displacement vector field, it can be seen that both expansive soil and modified soil samples have radial and vertical main cracks and secondary cracks develop during splitting and failure. The crack development morphology of expansive soil and modified soil samples with different initial water contents is basically the same. The research results in this study have reference significance for the stability control of similar projects.